The Sipepeg Application: Policy and Implementation in Social Welfare Administration Services - Nur Wulan Imadri; Sri Wulandari (Siber Nusantara Research, 2026)
This study looks at how social welfare administrative services are implemented at the Cirebon Regency Social Affairs Office using the Administrative Information System for Social Welfare Service Recipients (SIPEPEG). This study’s goal is to examine how digital-based social service policies are implemented, as well as the factors that support, hinder, and optimize them. This study’s goal is to examine how digital-based social service policies are implemented, as well as the factors that support, hinder, and optimize them. Van Meter and Van Horn’s policy implementation theory was used to analyze the study’s qualitative methodology, which include in-depth interviews, observation, and documentation. Although it hasn’t been fully optimized, the results show that SIPEPEG’s implementation has aided in streamlining social assistance administration. The main obstacles are lack of human resource, low public digital literacy, poor infrastructure, especially internet connectivity, technical issues with the application, limitations on the income deciles of aid recipients, and the length of the approval process. On the other hand, PUSKESOS employees’ dedication, interagency cooperation, the Social Affairs Office’s support, and public confidence all help to implement policies. Strengthened coordination, community support, capacity building for implementers, and preparations for the creation of a more integrated service system are all used to carry out optimization efforts.